Proximal Plantar Plate of Lesser Toe Metatarsophalangeal Joint Vascular Supply. (January 2023) - Park, Jiwon V.; Finney, Fred T.; Singer, Natalie V.; Saunders, Noah E.; Walley, Kempland C.; Holmes, James R.; Walton, David M.; Talusan, Paul G.
Background: The plantar plate is a major stabilizing structure of the metatarsophalangeal (MTP) joint with instability frequently occurring after a tear or attenuation of this structure. Commonly, a McGlamry elevator is used to strip the plantar plate from the plantar surface of the metatarsal to improve exposure of the MTP joint. The anatomy of the proximal plantar plate and vascular consequence of stripping the plantar plate from the metatarsal is not yet well understood. The purpose of this study is to describe the proximal attachment of the plantar plate anatomically and quantify the relative contribution of blood supply to the proximal plantar plate from both the metatarsal and the plantar fascia. Methods: For anatomic evaluation, 6 lower extremity cadaver specimens without any gross evidence of foot and ankle deformity were utilized. For imaging analysis, 16 fresh frozen human adult cadaveric lower extremity specimens were used for this study, resulting in 35 MTP joints without deformity and 11 lesser MTP joints with cockup and/or crossover deformities. The specimens were prepared as described previously by Finney et al. 5 Results: From gross anatomic dissection, the plantar plate origin consists of a stout fibrous pedicle distinct from the surrounding synovial-type tissue that firmly anchors the plantar plate to the metatarsal. Based on nano–computed tomographic imaging, an average of 63.5% of the vascular supply to the proximal portion of the plantar plate entered from the metatarsal pedicle. The remaining 36.5% of the vascular supply entered from the plantar fascia. Conclusion: The proximal attachment of the plantar plate includes a stout fibrous pedicle anchoring the proximal portion of the plantar plate to the notch between the medial and lateral plantar condyles of the metatarsal head. The vascular supply of the proximal plantar plate is supplied from both the metatarsal pedicle and plantar fascia. Level of Evidence: Level III, retrospective comparative study.